The ultimate low-calorie meals book : more than 400 light and healthy recipes for every day - Miller, Jan E. (Hoboken, N.J. : John Wiley & Sons, 2012)
'Healthy eating has never looked so good Featuring more than four hundred light and healthy, but unquestionably delicious, recipes, Ultimate Low-Calorie Meals is the go-to cookbook for both everyday meals and special occasions. Beautifully presented with over three hundred full-colour photographs, this collection includes up-to-date nutrition information on your favourite foods, taking the guesswork out of portion control.Covering a broad range of recipes organized in traditional categories, from everyday weeknight meals to special meals for gatherings with friends, cooks will find hundreds of recipes that prove, again and again, that they can enjoy delicious, food, without undermining their aim to maintain a healthy weight and feel great. Recipes include at-a-glance icons for Family Friendly dishes, 20-Minute Meals, and Share with Friends--perfect for holidays and special occasions Special features include savvy substitution charts showing readers how to switch in low-calorie alternatives in their everyday food choices Inspiring, up-to-date diet and nutrition advice Designed to help readers learn to eat well every day--not as a once-in-a-while diet, but as a lifetime lifestyle choice Monitoring calorie intake is a proven way of achieving and maintaining a healthy weight. The key is to monitor the number of calories consumed and the number of calories expended on a daily basis. This beautiful cookbook, with its magazine-like design--packed with luscious illustrations--makes keeping an eye on what you eat easy'--
'The Ultimate Low-Calorie Meals Book offers hundreds of recipes and ideas that make eating healthy and watching your weight easy and delicious. These recipes are ideal for light and nutritious everyday meals that form the basis of a healthy lifestyle. Filled with dishes the entire family will love, recipes are clearly marked with icons that let you quickly identify recipes that are ready in 30 minutes or less, high in fiber, and low in sodium'--
Includes index.
Keywords: Entrees (Cooking).; Low-fat diet -- Recipes; COOKING / Health & Healing / Weight Control